Enhanced photoelectrochemical stability of Ta3N5 in the acidic electrolyte conditions - Youn Chae, Sang; Duck Park, Eun (Applied Surface Science, 2022)
The unexpectedly improved photoelectrochemical activity and stability of the Ta3N5 photoelectrode in acidic electrolytes is first reported. The oxidation mechanism of the Ta3N5 surface is revealed as transpassivation, that the passive layer (TaNxOy) continuously grows from the film surface to the bulk side. The surface oxidation rate of Ta3N5 was suppressed in acidic electrolytes compared to basic pH conditions. The less formation of the passive layer at the Ta3N5 surface leads to improved photoelectrochemical activity and stability of Ta3N5 photoanode. Experiments on the TaNxOy layer formation at the Ta3N5/electrolyte interface revealed that interaction of the hydoroxonium ion with the N atom in Ta3N5 leads to the different behavior of the Ta3N5 photoelectrode. With suppressed TaNxOy formation under acidic pH conditions, the fast hole extraction from Ta3N5 photoanode by VO2+ ion enhanced the photoelectrochemical activity. This result indicates that Ta3N5 photoelectrode can be utilized under wide pH range conditions.
Keywords: Acidic electrolytes; Electrolyte conditions; Oxidation mechanisms; Passive layer; pH condition; Photo-anodes; Photoelectrochemical cell; Photoelectrochemicals; Photoelectrode; Transpassivation; Corrosion; Passive layer; Photoelectrochemical cell; Stability; Ta3N5